20 Progression of doppler-echocardiographic markers of structure and function in the personalised prospective comparison of arni with arb in patients with natriuretic peptide elevation (PARABLE) randomized controlled trial. (16th October 2019) - Ledwidge, M; Pharithi, RB; Ryan, F; Dodd, J; Murphy, D; Gallagher, J; Watson, C; Barrett, M; McDonald, K; Ferre, M
Abstract : Background: Elevated B-type NP (BNP) in asymptomatic patients with cardiac abnormalities can provide a protective, endogenous response to fibro-inflammation. The PARABLE study is investigating the hypothesis that augmenting BNP pharmacologically with the neutral endopepdidase inhibitor sacubitril can modulate progression of LAVI over 18 months measured using cardiac Magnetic Resonance Imaging (cMRI). In addition, all patients in PARABLE undergo Doppler-echocardiography at baseline, 9 months and 18 months. The purpose of this report is to evaluate overall, blinded progression of cardiac structural and functional abnormalities over 9 months in the first 100 and 18 months in the first 74 patients. Methods: PARABLE is an investigator-led, prospective, randomised, double blind, double dummy, phase II trial comparing treatment with sacubitril/valsartan versus valsartan. PARABLE will enroll 250 patients aged over 40 years with hypertension and/or diabetes, with BNP from 20–280 pg/mL or NTproBNP from 100 to 1000 pg/mL) and LAVI above 28 mL/m 2 . Excluded are patients with a history of heart failure, left ventricular systolic dysfunction, haemodynamically significant mitral and/or aortic valve disease, persistent atrial fibrillation, hepatic dysfunction and severe chronic kidney disease. The primary endpoint is change in LAVI measured by cMRI over 18 months. We evaluated blinded Doppler-echocardiographic measures of left ventricular structure, systolic function and diastolic function at baseline, 9 months and 18 months. Results: In the first 100 patients to complete the study, 35% were female, average age 72.7±8.0 years, 94% had hypertension and 22% had Type 2 diabetes. Sub-population blood pressure was 136/78±21/13 mmHg, heart rate was 63.5±10.8 bpm and body mass index was 28.8±4.9 kg/m 2 . Other baseline medical history included dyslipidaemia (83%), coronary artery disease (52%), other vascular disease (5%), stroke/TIA (10%), paroxysmal atrial fibrillation n (7%) and chronic kidney disease (2%). Median BNP was 79 pg/mL [interquartile range (IQR) 47, 117] and Baseline Doppler-echocardiography showed average ejection fraction was 68.5±6.5%, LVMI was 113.3±28.2%, E/e' was 11.3±3.2 and LAVI was 34.3±4.9 mL/m 2 . There were no significant changes from baseline in Doppler-echocardiography measures at 9 months. At 18 months, in the subgroup who had completed the study, the only observed change was a significant increase in LAVI from 34.0±4.6 mL/m 2 to 36.0±5.0 mL/m 2 (p<0.01). Conclusions: Participants in the PARABLE clinical trial with elevated BNP and LAVI at baseline show significant progression of LAVI abnormalities over an 18-month time period. The PARABLE study is on target to define the impact of preserving circulating BNP using sacubitril on LAVI progression as a personalised therapy for prevention of progression of left ventricular diastolic dysfunction.